Pengaruh Digital Marketing Dan Harga Terhadap Keputusan Pembelian Konsumen Pada Kopi Kenangan RC Veteran Jakarta Selatan - Naufal Hendriansyah; Ety Nurhayaty (Jurnal Manajemen, 2026)
The purpose of this study is to examine the partial and simultaneous effects of price and digital marketing on consumer purchasing decisions at Kopi Kenangan RC Veteran in South Jakarta. Multiple linear regression analysis was used as a quantitative tool in this study. Purposive sampling, which is based on Hair's formula, was the method used. 115 customers of Kopi Kenangan RC Veteran in South Jakarta participated in the survey. Questionnaires and a review of the literature were used to gather data. The Method of Successive Intervals (MSI) was used to convert ordinal data into interval data before statistical testing. Additionally, statistical analysis tests utilising the SPSS software. The study's findings show that price and digital marketing, both partially and concurrently, significantly and favourably influence customers' decisions to buy at Kopi Kenangan RC Veteran in South Jakarta.